<em>The</em><em> </em><em>answer</em><em> </em><em>is</em><em> </em><em>of</em><em> </em><em>option</em><em> </em><em>D</em><em>.</em>
<em>Hope</em><em> </em><em>this</em><em> </em><em>will</em><em> </em><em>help</em><em> </em><em>u</em><em>.</em><em>.</em><em>.</em><em>:</em><em>)</em>
Simplify both sides of the equation
x/16−(x+2/8) = 2x/16 + −1/8x + −1/4 = 2
Distribute
1/16x + −1/8x + −1/4 = 2
(1/16x + −1/8x)+(−1/4) = 2
Combine Like Terms
−1/16x + −1/4 = 2
Add 1/4 to both sides.
−1/16x + −1/4 + 1/4 = 2 + 1/4
−1/16x = 9/4
Multiply both sides by 16/(-1).
(16/−1)*(−1/16x)=(16/−1)*(9/4)
x=−36
Step-by-step explanation:
(64y100)1/2
1/2×64y 1/2×100
32y50
1) 15
2)6
3)9
Hope this helps!
Answer:
13/6 is the missing fraction
Step-by-step explanation:
well consider the missing integer as x
then 5/2 -x=1/3
so, -x=1/3 -5/2
-x = -13/6
x= 13/6